2022
DOI: 10.1242/jcs.259666
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling SARS-CoV-2 ORF6 localization and interferon antagonism

Abstract: Like many pathogenic viruses, SARS-CoV-2 must overcome interferon (IFN)-mediated host defenses for infection establishment. To achieve this, SARS-CoV-2 deploys overlapping mechanisms to antagonize IFN production and signaling. The strongest IFN antagonist is the accessory protein ORF6, which localizes to multiple membranous compartments, including the nuclear envelope, where it directly binds nuclear pore components Nup98-Rae1 to inhibit nuclear translocation of activated STAT1/IRF3 transcription factors. Howe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…Alternatively, if DVGs do not directly stimulate IFN production, they can suppress the expression of viral-encoding IFN antagonists by large deletions, resulting in an earlier and higher IFN expression in DVG+ cells. Indeed, IFN antagonists are encoded in NSP1, NSP3, NSP5, NSP12, NSP13, NSP14, NSP15, ORF3a, ORF3b, ORF6, ORF7a, ORF7b, ORF8, ORF9b, N, and M (Lei, Dong et al 2020, Xia, Cao et al 2020, Han, Zhuang et al 2021, Wong, Cheung et al 2022, Znaidia, Demeret et al 2022) and most of them are within the deletion regions based on our conserved genomic hotspots for DVG recombination sites (Fig. 2A and 2B).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if DVGs do not directly stimulate IFN production, they can suppress the expression of viral-encoding IFN antagonists by large deletions, resulting in an earlier and higher IFN expression in DVG+ cells. Indeed, IFN antagonists are encoded in NSP1, NSP3, NSP5, NSP12, NSP13, NSP14, NSP15, ORF3a, ORF3b, ORF6, ORF7a, ORF7b, ORF8, ORF9b, N, and M (Lei, Dong et al 2020, Xia, Cao et al 2020, Han, Zhuang et al 2021, Wong, Cheung et al 2022, Znaidia, Demeret et al 2022) and most of them are within the deletion regions based on our conserved genomic hotspots for DVG recombination sites (Fig. 2A and 2B).…”
Section: Discussionmentioning
confidence: 99%
“…To date, structural information on ORF6 protein has been limited to its existence as a complex comprising a C-terminal tail, Rae1, and Nup98. , According to our earlier study, ORF6 protein existed either in clusters or in large aggregates, localized in the perinuclear region rather than confined in the nuclear rim. Using counterstaining, Wong et al demonstrated that ORF6 protein resides on the endoplasmic reticulum (ER), Golgi apparatus, and mitochondria. We hypothesize that ORF6 protein could aggregate and form a shield at the perinuclear region to trap host nucleoporins (Rae1 and Nup98) or sequester nuclear transport receptors (karyopherins α). , This hypothesis could explain the cytoplasmic retention of nucleoporins and impaired nuclear import in ORF6-expressing cells. Moreover, a similar mechanism has been reported for SARS-CoV ORF6 protein .…”
mentioning
confidence: 75%
“…Several studies, including ours, have demonstrated that the subcellular localization of ORF6 protein is not confined to the nuclear rim. 5,14,38 Instead, ORF6 protein appeared as aggregates that localized on membranous organelles, including ER, Golgi apparatus, mitochondria, lysosomes, and autophagosomes. 38 Several studies have reported Alzheimer's disease (AD)-like neurological complications in COVID-19 patients (reviewed in ref 39).…”
mentioning
confidence: 99%
“…ORF6 has been reported to dislocate Rae1 and Nup98 from the NPC, but whether this mislocalisation causes the mRNA export block or is a consequence of mRNA export disruption is not known [25]. A very recent paper suggests that although overexpressed ORF6 is localised to membranes, it is only a peripheral membrane protein (not transmembrane), and that ORF6 mis-localised proteins were still able to block nuclear trafficking [29]. Furthermore, in a recent preprint, Yoo et al also report that membrane localisation is dispensable for nuclear transport [30].…”
Section: Discussionmentioning
confidence: 99%